Disparities in rheumatoid arthritis disease activity according to gross domestic product in 25 countries in the QUEST–RA database. Issue 11 (30th July 2009) - Sokka, T; Kautiainen, H; Pincus, T; Toloza, S; da Rocha Castelar Pinheiro, G; Lazovskis, J; Hetland, M L; Peets, T; Immonen, K; Maillefert, J F; Drosos, A A; Alten, R; et al.
Abstract : Objective: To analyse associations between the clinical status of patients with rheumatoid arthritis (RA) and the gross domestic product (GDP) of their resident country. Methods: The Quantitative Standard Monitoring of Patients with Rheumatoid Arthritis (QUEST–RA) cohort includes clinical and questionnaire data from 6004 patients who were seen in usual care at 70 rheumatology clinics in 25 countries as of April 2008, including 18 European countries. Demographic variables, clinical characteristics, RA disease activity measures, including the disease activity score in 28 joints (DAS28), and treatment-related variables were analysed according to GDP per capita, including 14 "high GDP" countries with GDP per capita greater than US24 000 and 11 "low GDP" countries with GDP per capita less than US11 000. Results: Disease activity DAS28 ranged between 3.1 and 6.0 among the 25 countries and was significantly associated with GDP (r = −0.78, 95% CI −0.56 to −0.90, r 2 = 61%). Disease activity levels differed substantially between "high GDP" and "low GDP" countries at much greater levels than according to whether patients were currently taking or not taking methotrexate, prednisone and/or biological agents. Conclusions: The clinical status of patients with RA was correlated significantly with GDP among 25 mostly European countries according to all disease measures, associated only modestly with the current use of antirheumatic medications. The burden of arthritis appears substantially greater in "low GDP" than in "high GDP" countries. These findings may alert healthcare professionals and designers of health policy towards improving the clinical status of patients with RA in all countries.